2011
DOI: 10.1007/s10728-011-0199-3
|View full text |Cite
|
Sign up to set email alerts
|

Who Cares? Moral Obligations in Formal and Informal Care Provision in the Light of ICT-Based Home Care

Abstract: An aging population is often taken to require a profound reorganization of the prevailing health care system. In particular, a more cost-effective care system is warranted and ICT-based home care is often considered a promising alternative. Modern health care devices admit a transfer of patients with rather complex care needs from institutions to the home care setting. With care recipients set up with health monitoring technologies at home, spouses and children are likely to become involved in the caring proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…The tendency for this group is to age independently at home (or 'age-in-place'), instead of going into assisted-living or nursing homes [1]. The care for these older adults who are living at home is often provided by (formal) professional healthcare providers and informal caregivers (family members or friends).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendency for this group is to age independently at home (or 'age-in-place'), instead of going into assisted-living or nursing homes [1]. The care for these older adults who are living at home is often provided by (formal) professional healthcare providers and informal caregivers (family members or friends).…”
Section: Introductionmentioning
confidence: 99%
“…This makes it unlikely for them to be reached by informal care organisations that offer supportive resources, such as respite care [3]. While the role of these informal caregivers is becoming more and more important as there is an increasing shift from institutional care to home care [4], their interests are often ignored in discussions about the future of healthcare [1]. To address this lack, this paper discusses the literature and study of a system that aims to unburden the informal caregivers and empower the older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Visits from medical personnel and carers may be less necessary if daily monitoring of conditions is controlled by H-IoT (Demiris et al 2004;Stowe and Harding 2010;Tiwari et al 2010;Wu et al 2012). Studies involving older people have revealed a concern that H-IoT will replace personal and social interactions with carers (Chan et al 2008;McLean 2011;Palm 2011;Zwijsen et al 2011;Wu et al 2012) rather than merely supplementing them, as it is often promised. Collection of contextual information about a patient's condition via face-to-face interactions can be difficult to replicate with sensors (Percival and Hanson 2006; see "'Good' care and user well-being" section).…”
Section: Social Isolationmentioning
confidence: 99%
“…As it stands, patients' trust will be misplaced so long as equivalent norms of practice for providing healthcarevia-monitoring remain unspecified. Such norms require the communication of role-based obligations to new care providers, both informal carers and providers of H-IoT devices and services, including dialogue to define appropriate codes of conduct and related principles of good practice in H-IoT mediated informal care (Palm 2011;Mittelstadt et al 2014). Alternatively, it can be argued that 'good medicine ' (cf.…”
Section: Risks Of Non-professional Carementioning
confidence: 99%
“…H-IoT is often viewed as a technological means to reduce the costs or need for professionals in medical and social care, while still providing comparable care. The user's quality of care, and physical and social well-being, are therefore at risk [65,[96][97][98][99]. A combination of sensors, H-IoT service providers, healthcare professionals and informal caregivers may not provide equivalent quality of care, particularly in social and interpersonal aspects of care.…”
Section: Meet Professional Duties Of Care and Facilitate Inclusion Ofmentioning
confidence: 99%